Analysis Of The Qualifications Of The First Class Arabic Teaching Book By Yudhistira - Nur Yusrin Hidayanti, Primasti; Maturedy, Faris; Zinatul Hamidah, Noor (UIN Maulana Malik Ibrahim Malang, 2025)
The objective of this study is to assess the accuracy and reliability of the Arabic language textbooks used in the first grade of Madrasah Ibtidaiyah at Yudhistira School in 2021. The assessment will be conducted according to the established guidelines set by the National Educational Standards Agency (BSNP). This study employs a qualitative research methodology using a quasi-qualitative technique. Regarding this particular research, it primarily involved library research. The main source utilized for producing this research was the Arabic edition of Yudhistira. This study employs content analysis methodology, hence its conclusions will mostly concentrate on the assessment of the accuracy and presentation of the material utilized in Arabic language books. The findings of this study suggest that the Yudhistira edition of the Madrasah Ibtidaiyah grade 1 Arabic language textbook falls into the category of being acceptable for use. Nevertheless, during this investigation, many shortcomings were identified that require rectification in order to ensure the textbook's impeccable suitability for use. employed in the acquisition of Arabic language skills. The book has two main shortcomings: it does not integrate cultural components in its content, and it fails to offer tangible indicators in each chapter.